2012
DOI: 10.1245/s10434-012-2603-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-type and Pancreatobiliary-type Adenocarcinomas: How Does Ampullary Carcinoma Differ from Other Periampullary Malignancies?

Abstract: Long-term survival for patients with ampullary carcinomas equals pancreatic, biliary, and duodenal carcinomas when the same histologic type is compared. It can be questioned whether ampullary carcinomas should be regarded as a separate entity in classification of solid tumors. Clinical trials on adjuvant treatments for periampullary carcinomas should stratify by pancreatobiliary type versus intestinal type of histologic differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
89
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 31 publications
8
89
2
1
Order By: Relevance
“…according to criteria previously reported. 4,5,15 In brief, IT-PapCa was defined by tubular to elongated glands, cribriform, or solid nests of columnar cells with pseudostratified nuclei closely resembling colorectal adenocarcinoma (Fig 2, F). PT-PapCa consists of simple or branching glands as well as solid nests of mainly cuboidal cells with a high degree of nuclear pleomorphism surrounded by striking desmoplastic stroma (Fig 2, E).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…according to criteria previously reported. 4,5,15 In brief, IT-PapCa was defined by tubular to elongated glands, cribriform, or solid nests of columnar cells with pseudostratified nuclei closely resembling colorectal adenocarcinoma (Fig 2, F). PT-PapCa consists of simple or branching glands as well as solid nests of mainly cuboidal cells with a high degree of nuclear pleomorphism surrounded by striking desmoplastic stroma (Fig 2, E).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Indeed, among patients with PapCa, there is a broad interindividual range of outcomes that impairs the prediction of specific outcomes and clinical decision making as to individual adjuvant therapy. [6][7][8][9][10][11] Kimura et al 12 suggested to subdivide PapCa into intestinal type (IT) and pancreaticobiliary type (PT) emphasizing those as main tumor ''subtypes.''…”
mentioning
confidence: 99%
“…Moreover, molecular classification makes it possible to observe different biological behaviors and distinguish two subtypes of AAC based on immunohistochemistry Chu et al 2005;Sessa et al 2007;Amptoulach et al 2011;Westgaard et al 2013). Specially, the intestinal epithelial-specific marker, caudaltype homeodomain transcription factor 2 (CDX2) was an independent good prognostic marker for resected AAC (Hansel et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The patients suffering from adenocarcinoma of intestinal type do better than patients with adenocarcinoma of pancreatobiliary type (Albores-Saavedra et al, 2007, Westgaard et al, 2008. Patients with tumors of the same histological subtype, but from different anatomical site of origin, have similar overall survival (Westgaard et al, 2013). Due to the differences in pathogenesis and survival, accurate histological classification of the periampullary adenocarcinomas is crucial for an adequate prognostic estimation and an individualized therapeutic decision.…”
Section: Introductionmentioning
confidence: 99%